Micromorphology of glacial sediments - John Hiemstra (Reference Module in Earth Systems and Environmental Sciences, 2023)
Since its introduction in the 1980s, micromorphology has proved invaluable in its application to glacial sediments. Particularly where visible exposures are limited, such as in sediment cores, there may be a need for detailed information, which cannot be provided by conventional sedimentological techniques. Micromorphology entails the qualitative and quantitative study of thin sections under a transmitted-light petrographic microscope. Using relatively low magnifications, undisturbed sediment samples of glacial sediments can be analyzed in both plane- and cross-polarized light. The visual and computer-assisted analyses of texture, micro-structure, micro-fabric and plasmic fabric allows for interpretations in terms of depositional and deformational history, which is often critical for the reliable reconstruction of Quaternary environments based on the preserved glacial sedimentary records.